Strengthening Indonesian Culinary UMKM for the PARI Community in Malaysia to Improve Economic Income - Winda Anggraini; Asep Kusmawan; Miming Arjuni (TAKHADUM: Jurnal Penelitian & Pengabdian kepada Masyarakat, 2026)
This community service program aims to strengthen Indonesian culinary UMKM within the PARI community in Malaysia through digital marketing training, branding enhancement, business management assistance, and entrepreneurial mentoring. The program employed a participatory approach involving observations, interviews, training sessions, direct mentoring, and program evaluation involving Indonesian diaspora culinary entrepreneurs in Malaysia. The results demonstrate that participants experienced significant improvements in digital literacy, product branding, financial management, and entrepreneurial capacity. Participants began utilizing digital platforms such as Instagram, TikTok, Facebook, and WhatsApp Business to expand market reach and improve customer engagement. In addition, improvements in packaging design, branding strategies, and financial recordkeeping contributed to increasing product competitiveness and business sustainability. The program also generated positive economic impacts through increased sales and customer numbers among participants. This study confirms that integrative and participatory empowerment models are effective strategies for strengthening diaspora-based culinary UMKM and improving the economic welfare of Indonesian migrant communities in Malaysia.